Aplikasi Finishing Rustic Style untuk Galeri, Kafe dan Retail - S.P. Honggowidjaja, Elvira Dwi Jayanti (Intra, 2014)
Interior Design Gallery, Cafe and Retail Nostalgia is designed with the goals and expectations in order to be useful to the community as a place of entertainment, information, and education in the same, especially people who ever existed in the era of 1960-1990. Interior design galleries, cafes and retail will generate a nostalgic Â is scheduled to be build in Surabaya, in the central part of the city area and the hotel Tunjungan and Majapahit. This location was chosen for the strategic place design and prospects, the location in a crowded area with high historical values, so that it communities and tourist. In an effort to be able to realize this design then takes several steps to meet the design requirements. The first stage is to find data that is needed to complete the design. As with literature data, the data typology as a comparison among other are kopitiam 88 in Surabaya, Surabaya Ourbar, The Bistrot in Seminyak Bali, and Cosmic Diner on Sunset Road in Bali.